Fractional Excretion of Urea in Pre-eclampsia: a Clinical Observation (Iranian Journal of Kidney Diseases, 2011)
Introduction. Pre-eclampsia is one of the leading causes of maternal and fetal mortality and morbidity. It occurs in 7% of all the pregnancies and accounts for 80% of the cases of pregnancy-induced hypertension. Diagnosis of pre-eclampsia in patients with pre-existing chronic kidney disease, proteinuria, and hypertension is a dilemma.  The fractional excretion of urea has been described as a marker for renal perfusion. Since pre-eclampsia is associated with a marked decline in renal perfusion, we explored the utility of the fractional excretion of urea as a marker for pre-eclampsia. Materials and Methods. Urine and serum chemistries were evaluated in 6 pregnant women with pre-eclampsia on their first visit, immediately prior to delivery, and postpartum. For each of these three measurements, the fractional excretion of urea was calculated and proteinuria was assessed by random urine protein-creatinine ratio or 24-hour urine protein studies. Results. In patients diagnosed with pre-eclampsia, the fractional excretion of urea decreased substantially from higher values obtained during the 3rd trimester to values consistent with renal hypoperfusion (< 35%) just prior to delivery, and it rapidly normalized immediately after delivery. Conclusions. Alterations in fractional excretion of urea, which suggest a decreased renal perfusion, may be a useful tool in supporting the diagnosis of preeclampsia.